Radiogenic isotopes in enriched mid-ocean ridge basalts from Explorer Ridge, northeast Pacific Ocean. (15th September 2017) - Cousens, Brian; Weis, Dominique; Constantin, Marc; Scott, Steve
Abstract: Extreme gradients in topography related to variations in magma supply are observed on the Southern Explorer Ridge (SER), part of the northern Juan de Fuca ridge system. We report radiogenic isotope (Pb, Sr, Nd, Hf) and geochemical data for twenty-four basalt whole-rock and glass samples collected from the length of the SER and from Explorer Deep, a rift to the north of the SER. Lavas from the SER form a north-south geochemical gradient, dominated by E-MORB at the northern axial high, and range from T-MORB to N-MORB towards the southern deepest part of the ridge. Linear relationships between incompatible element ratios and isotopic ratios in MORB along the ridge are consistent with mixing of magmas beneath the ridge to generate the geographic gradient from E- to N-MORB. The E-MORB have high Sr and Pb, and low Nd and Hf isotopic ratios, typical of enriched mantle that includes a FOZO or HIMU isotopic component. The West Valley and Endeavour segments of the northern Juan de Fuca ridge also include this isotopic component, but the proportion of the FOZO or HIMU component is more extreme in the SER basalts. The FOZO or HIMU component may be garnet-bearing peridotite, or a garnet pyroxenite embedded in peridotite. Recycled garnet pyroxenite better explains the very shallow SER axial high, high Nb/La and La/Sm, and the "enriched" isotopic compositions.